Ephedra alte (Joint Pine): An Invasive, Problematic Weedy Species in Forestry and Fruit Tree Orchards in Jordan - Jamal R. Qasem (The Scientific World Journal)
A field survey was carried out to record plant species climbed by Ephedra alte in certain parts of Jordan during 2008–2010. Forty species of shrubs, ornamental, fruit, and forest trees belonging to 24 plant families suffered from the climbing habit of E. alte. Growth of host plants was adversely affected by E. alte growth that extended over their vegetation. In addition to its possible competition for water and nutrients, the extensive growth it forms over host species prevents photosynthesis, smothers growth and makes plants die underneath the extensive cover. However, E. alte did not climb all plant species, indicating a host preference range. Damaged fruit trees included Amygdalus communis, Citrus aurantifolia, Ficus carica, Olea europaea, Opuntia ficus-indica, and Punica granatum. Forestry species that were adversely affected included Acacia cyanophylla, Ceratonia siliqua, Crataegus azarolus, Cupressus sempervirens, Pinus halepensis, Pistacia atlantica, Pistacia palaestina, Quercus coccifera, Quercus infectoria, Retama raetam, Rhamnus palaestina, Rhus tripartita, and Zizyphus spina-christi. Woody ornamentals attacked were Ailanthus altissima, Hedera helix, Jasminum fruticans, Jasminum grandiflorum, Nerium oleander, and Pyracantha coccinea. Results indicated that E. alte is a strong competitive for light and can completely smother plants supporting its growth. A. communis, F. carica, R. palaestina, and C. azarolus were most frequently attacked.